2009
DOI: 10.4076/1757-1626-2-8793
|View full text |Cite
|
Sign up to set email alerts
|

Closed subtalar dislocation with non-displaced fractures of talus and navicular: a case report and review of the literature

Abstract: Closed subtalar dislocations associated with talus and navicular fractures are rare injuries. We report on a case of a 43-year-old builder man with medial subtalar dislocation that was further complicated by minimally displaced talar and navicular fractures. Successful closed reduction under general anesthesia was followed by non-weight bearing and ankle immobilization with a below-knee cast for 6 ;weeks. At 3 years post-injury, the subtalar joint was stable, the foot and ankle mobility was in normal limits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, in cases which are non-reducible by closed procedure; it is recommended to proceed with open reduction and internal fixation under general anesthesia and a short leg cast immobilization for 4-6 weeks. 7 Optimal management begins with a full assessment of the patient and formulating the anesthesia plan. The strategy for patient care in the perioperative period should be tailored according to the individual and the surgical procedure involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases which are non-reducible by closed procedure; it is recommended to proceed with open reduction and internal fixation under general anesthesia and a short leg cast immobilization for 4-6 weeks. 7 Optimal management begins with a full assessment of the patient and formulating the anesthesia plan. The strategy for patient care in the perioperative period should be tailored according to the individual and the surgical procedure involved.…”
Section: Discussionmentioning
confidence: 99%
“…Avascular necrosis of the talus is rare given that the talus has not been dissociated from the ankle mortise, therefore most of its blood supply is maintained from the deltoid ligament 6. Most patients will have some degree of pain and stiffness of the subtalar joint and some degree of osteoarthritis following these injuries 7. Closed subtalar dislocation generally has a good functional outcome 7.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients will have some degree of pain and stiffness of the subtalar joint and some degree of osteoarthritis following these injuries 7. Closed subtalar dislocation generally has a good functional outcome 7. However, when associated with tarsal fractures, higher rates of ankle arthrodesis secondary to traumatic osteoarthritis are observed 8.…”
Section: Discussionmentioning
confidence: 99%
“…Fotiadis et al 3 have reported on a medial subtalar dislocation with non-displaced fractures of the talar body and navicular (figure 1). …”
Section: Descriptionmentioning
confidence: 99%